2018
DOI: 10.1016/j.jvs.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

2018 Guidelines for the Early Management of Patients With Acute Ischemic Stroke: A Guideline for Healthcare Professionals From the American Heart Association/American Stroke Association

Abstract: Emergency medical services (EMS) use by stroke patients by calling 911 has been independently associated with earlier emergency department (ED) arrival (onset-to-door time #3 hours), quicker ED evaluation (more patients with door-to-imaging time #25 minutes), and more eligible patients being treated with IV alteplase. However, only w60% of all stroke patients use EMS and is less likely used by men, blacks, and Hispanics. Although EMS prenotification was associated with increased likelihood of alteplase treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
1,198
4
47

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 778 publications
(1,261 citation statements)
references
References 0 publications
12
1,198
4
47
Order By: Relevance
“…Moreover, for NIHSS score at admission, we classified more than half of the patients who had unfavourable functional outcome using a threshold of 12. Meanwhile, those with a NIHSS score ≥12 at admission had a 4.7-folded risk of unfavourable functional outcome with rt-PA treatment compared with those whose NIHSS score <12, although prior evidence suggested that rt-PA should be used for patients with AIS whose NIHSS scores≤25 at admission when other eligibility criteria are met 1. Therefore, detailed cerebrovascular imaging examination should be completed as soon as possible and therapeutic strategy such as mechanical thrombectomy can be largely considered for patients with a NIHSS score ≥12 at admission, especially when there are indications of mechanical thrombectomy, such as age ≥80 years 1…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, for NIHSS score at admission, we classified more than half of the patients who had unfavourable functional outcome using a threshold of 12. Meanwhile, those with a NIHSS score ≥12 at admission had a 4.7-folded risk of unfavourable functional outcome with rt-PA treatment compared with those whose NIHSS score <12, although prior evidence suggested that rt-PA should be used for patients with AIS whose NIHSS scores≤25 at admission when other eligibility criteria are met 1. Therefore, detailed cerebrovascular imaging examination should be completed as soon as possible and therapeutic strategy such as mechanical thrombectomy can be largely considered for patients with a NIHSS score ≥12 at admission, especially when there are indications of mechanical thrombectomy, such as age ≥80 years 1…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant tissue plasminogen activator (rt-PA) is currently the most standard and recommended intravenous thrombolytic therapy for patients diagnosed with acute ischaemic stroke (AIS) 1. The efficacy of rt-PA in improving poststroke functional outcome and preventing deaths has been proved in a number of trials 2.…”
Section: Introductionmentioning
confidence: 99%
“…More valid assays, such as factor Xa concentrations (for apixaban, edoxaban and rivaroxaban) and dilute thrombin time (dabigatran) are not usually available quickly. In the absence of an assay result excluding a significant effect of a DOAC, US guidelines advise against thrombolysis unless it can be clearly established that the patient last took the medication more than 48 hours ago and has normal renal function 27. The European Society of Cardiology recommends also considering thrombolysis for patients who last took a DOAC between 24 and 48 hours ago, if renal function is normal and they are otherwise a good candidate 95.…”
Section: Common Challenges During Anticoagulationmentioning
confidence: 99%
“…Endovascular thrombectomy using a stent retriever with or without preceding intravenous thrombolysis is now accepted as a standard treatment for selected patients with acute ischemic stroke due to intracranial large vessel occlusions 1. Despite its efficacy, endovascular thrombectomy is more likely to increase hemorrhagic complications than conservative management 2–4…”
Section: Introductionmentioning
confidence: 99%